A Method to Study Honey Bee Foraging Regulatory Molecules at Different Times During Foraging - Singh, Asem Surindro; Takhellambam, Machathoibi Chanu (Frontiers in Insect Science, 2021)
The foraging of honey bees is one of the most well organized and admirable behaviors that exist among social insects. In behavioral studies, these beautiful insects have been extensively used for understanding time-space learning, landmark use and concept of learning etc. Highly organized behaviors such as social interaction and communication are systematically well organized behavioral components of honeybee foraging. Over the last two decades, understanding the regulatory mechanisms underlying honey bee foraging at the cellular and molecular levels has been increasingly interested to several researchers. Upon the search of regulatory genes of brain and behavior, immediate early (IE) genes are considered as good tool to begin the search investigation. Our two recent studies, have demonstrated three IE genes namely Egr-1, Hr38 and kakusei having a role in the daily foraging of bees and their association with learning and memory during the foraging. These studies further evidence that IE genes can be used as a tool in finding the specific molecular/cellular players of foraging in honey bees and its behavioral components such as learning, memory, social interaction, social communication etc. In this article we provide the details of the method of sample collection at different times during foraging to investigate the foraging regulatory molecules. Key words: Honey bee foraging, learning and memory, immediate early genes, Egr-1, Hr38, Kakusei.